Governing higher education today : international perspectives - Strike, Tony; Nicholls, Jonathan 1956-; Rushforth, John (Routlledge, Taylor & Francis Group, 2019)
"Higher Education Governance in a Changing Environment provides an analysis of the longer-term dynamics and policy trends in a world market for higher education, and the emerging national responses which are likely to shape institutional governance in the next decade. The book is a forward-looking, thoughtful analysis of the trends and strategic directions in governance and policy in higher education with an international perspective presenting insights from practicing thought leaders on its future. It will be an essential resource for all who work in Higher Education, particularly those who sit on governing bodies or work in university leadership or policy roles"--
Keywords: vysoké školy -- mezinárodní kontext; management školy; strategický management; vzdělávací politika; universities and colleges -- international context; school management; strategic planning; educational policy; kolektivní monografie; collective monographs